If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-7n + 1) = -33 + -7n Reorder the terms: 2(1 + -7n) = -33 + -7n (1 * 2 + -7n * 2) = -33 + -7n (2 + -14n) = -33 + -7n Solving 2 + -14n = -33 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. 2 + -14n + 7n = -33 + -7n + 7n Combine like terms: -14n + 7n = -7n 2 + -7n = -33 + -7n + 7n Combine like terms: -7n + 7n = 0 2 + -7n = -33 + 0 2 + -7n = -33 Add '-2' to each side of the equation. 2 + -2 + -7n = -33 + -2 Combine like terms: 2 + -2 = 0 0 + -7n = -33 + -2 -7n = -33 + -2 Combine like terms: -33 + -2 = -35 -7n = -35 Divide each side by '-7'. n = 5 Simplifying n = 5
| 0.4x-0.2(2-2x)=-0.7(x-8) | | -5(8k+1)=315 | | 6(17z-2)=-5(-18z+12) | | 14.1-W= | | -20+19n-20=-6(-13n-20)-19n | | 2x^2+19x=6x+7 | | -4(b-6)=-24+2b | | 3(10w-18)=14w+10+8w | | 90=6(3m-2)-6 | | y-(-7)=5 | | -2f-7(19f+17)=8(7f+9) | | 7x-3=X+12 | | 6(m-3)=-20+7m | | -19.03-16.6u=-15.5u | | 3k-6(3-k)=-90 | | -18q-2(-2q+17)=20q | | 3p+5p=-8 | | -8=6+y | | 1+5x-4x=7 | | 4(-3p-20)=-19p+18 | | -3+8=35 | | -20m+18+19=17-5(5m-18) | | 0.7x-16=1.4x-23 | | -16.5-18.2n=9.1-16.2n | | k+k-k=7 | | 72-s=26 | | -2(-12-15b)=3(-10+b) | | 5y=8x-6 | | -3a-6-1=-1 | | -5(4m+2)=-6m+32 | | 16d-20d+-6d+5d=15 | | -15j=-5(4j+2) |